Group Leader-Following Consensus Control for Heterogeneous Multi-Agent Systems With Time Delays - Chong Tan (IEEE Access, 2021)
In this paper, the problem of group leader-following consensus is discussed for high-order heterogeneous multi-agent systems(HMASs) with multiple leaders and time delays. The four situations are considered: autonomous leaders, active leaders with controllers, and accepting their own information with/without time delays. Different protocols are designed for different situations. Under the corresponding protocols, HMASs can achieve group leader-following consensus without the limitation of in-degree balance. And the networked predictive scheme(NPS) actively compensating for time delays is used to predict current information of agents. Besides, the results are extended to multiple groups case. Finally, the simulation results show that, based on the NPS, the state trajectory of each agent in the time-delay case is very close to that in no time-delay case.